Simple Disulfides: Studies of Some Exponents of a Family Involved in Prominent Processes - Cayón, Vanina Mabel (2023)
Exploring the fundamental chemistry and intrinsic properties of disulfide-containing species has become an increasingly popular means to understand their action in various scientific fields, applications, and systems. In this study several representatives of this extensive family with the general formula CCl3SSR, where R represents CH2CH3, CH2CF3, C(CH3)3, C6H5 and C(O)CH3,were prepared and characterized by vibrational spectroscopy methods (FTIR and Raman), NMR spectroscopy, mass spectrometry, X-ray structure determinations and photo electron spectroscopy. When complemented with computational chemistry, this range of methods and techniques sheds new light on numerous different processes. It is worth noting that the importance in disulfides compounds is related to inherent properties of this chemical family, such as chirality, theories involving the origin of life and its evolution, and, lately, the mechanisms of S−S bond formation in processes concerning therapies based on the use of peptides and COVID-19.